Nepal’s National REDD Framework: How to Start? - Kotru, Rajan (Journal of Forest and Livelihood, 2009)
This paper examines the Government of Nepal's policy on climate change, especially its recent initiative to join the World Bank's Forest Carbon Partnership Facility (FCPF). The FCPF was established after the 13th Conference of the Parties in Bali adopted Reducing Emissions from Deforestation and forest Degradation (REDD) as the most efficient and effective strategy for mitigating climate change. This paper is based on close observations and insights from the government's attempts to enter the FCPF scheme and the multi?stakeholder consultative process. Despite some genuine concern, REDD may provide opportunities for institutionalizing good governance in the forestry sector. Moreover, it might help build the institutional and technical capacities of the stakeholders to benefit from the emerging global carbon trade. Despite several challenges, it provides a means for preparing Nepal as a potential player in the market. Suggestions are made to make it a successful pro?poor initiative capable of simultaneously addressing climate change and poverty issues. Key words: FCPF, IEC, REDD, stakeholders, climate change Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.51-55